Novel eco-friendly maleopimaric acid based polysiloxane flame retardant and application in rigid polyurethane foam. (29th September 2020) - Wang, Shibo; Yang, Xinxin; Li, Zhaoshuang; Xu, Xu; Liu, He; Wang, Dan; Min, Huihua; Shang, Shibin
Abstract: Polysiloxane flame retardants have been widely studied because of their high heat resistance and nontoxicity. The flame retardant efficiency may be further improved by inhibiting the release of cyclic siloxanes during combustion. In this study, a novel flame retardant was synthesised by imidisation of an amino-polysiloxane using biorenewable resource-maleopimaric acid (MPA). The MPA inhibits the conversion of polysiloxane to cyclic siloxane, thereby enhancing thermal stability. The synthesised flame retardant was employed as a part of the soft segment to produce rigid polyurethane foam (RPUF) by a "one-pot" process. The rigid MPA and imide groups inhibit the "back-bite" of polysiloxane and promote the formation of a silica-rich hybrid char layer on the backbone of RPUF to reduce flammability. Compared with pure RPUF, the minimum oxygen concentration necessary to support the combustion of modified foam increased by 39.7%, and the peak heat release rate (PHRR) of modified RPUF decreased by more than 50%. Simultaneously, the imide groups and the rigid hydrogenated phenanthrene ring of MPA improved the compressive strength of polysiloxane-modified RPUF. The technique to synthesise a highly effective polysiloxane flame retardant for RPUF is given herein. Graphical abstract: Image 1 Highlights: A novel maleopimaric acid-modified polysiloxane flame retardant was synthesised. The synthesised flame retardant was integrated into a rigid polyurethane foam. The rigid MPA and imide groups inhibit the "back-bite" of polysiloxane. They also promote the formation of a silica-rich hybrid char layer.